Experiences of cancer patients in a patient navigation program: a qualitative systematic review. - Tan, C.; Wilson, S.; McConigley, Ruth (2015)
BACKGROUND: A patient navigation program is a model of care which entails trained personnel providing individualized and assistive care to adult oncology patients to help the patients overcome barriers. A further aim of the program is to achieve continuity of care as patients experience the complex healthcare system. Patient navigation is a new model of care in many institutions, and as such the experiences of patients in the patient navigation program remains inconclusive. OBJECTIVES: The review seeks to understand the experiences of adult patients in patient navigation programs and how patient navigators impact the challenges patients encounter in the cancer care continuum. INCLUSION CRITERIA: TYPES OF PARTICIPANTS:   Participants of interest were adult cancer patients more than 18 years of age who are receiving or have received cancer care and are in a patient navigation program or had been in a hospital patient navigation program.  Types of intervention(s)/phenomena of interest:  The phenomenon of interest was the experiences of adult cancer patients who used patient navigation programs in hospital including how patient navigators impact on the challenges patients encounter in the cancer care continuum.  Types of studies:  This review considered studies that focused on qualitative data including, but not limited to, designs such as phenomenology, grounded theory, action research and exploratory studies.  CONTEXT:   The review includes patient navigation programs within a hospital setting.  Types of outcome:  The review sought to understand the experiences of patients with cancer in patient navigation programs in the hospital. SEARCH STRATEGY: A three-step search strategy was used. An initial search to identify keywords was undertaken in PubMed and Science Direct followed by an expanded search using all identified keywords and index terms specific to each included database. The reference lists of included papers were then searched for any other relevant studies. METHODOLOGICAL QUALITY: Each paper was assessed independently by two reviewers for methodological quality using the Joanna Briggs Institute Qualitative Assessment and Review Instrument. Any disagreements that arose between the reviewers were resolved through discussion. DATA COLLECTION: Data extraction and synthesis was conducted using standardized data extraction and synthesis tools from JBI-QARI. DATA SYNTHESIS: The 17 unequivocal and credible findings of included studies were categorized according to similarity of meaning and developed into three synthesized findings. RESULTS: Three papers were included in the review. The three synthesized findings from the 17 findings extracted from the papers were: (1) Emotional empowerment: patient navigators need to be present with patients at key phases of the cancer care continuum and assure patients of their accessibility; (2) Knowledge empowerment: patient navigators need to explore and manage the needs and expectations of patients so that the healthcare team and patient have the same understanding of treatment goals and plans; and (3) Bridging the gaps: patient navigators need to ensure practical assistance is provided for patients to ensure continuity of care even at the completion of the treatment regimen. CONCLUSIONS: The presence of a patient navigator provides strong support to the patients when experiencing disruption from cancer diagnosis and treatment. The emotional isolation they experience lessens with the assurance that there is always a consistent and constant contact point they can fall back on. The logistic and practical help given by the navigators allows patients to take time to process information and make sense of what is happening.